2001
DOI: 10.1046/j.1365-2168.2001.01732.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and survival after hepatic resection for hepatocellular carcinoma without cirrhosis

Abstract: In the treatment of HCC without cirrhosis, major hepatectomy is advocated to prevent early recurrence. Liver transplantation may be required for patients with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
6
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 25 publications
6
87
6
6
Order By: Relevance
“…A recent study showed, that hepatitis C virus infection is associated with increased risk of intrahepatic recurrence after HR of HCC in patients without cirrhosis. 21 However, in patients with cirrhosis, the etiology of liver disease appeared not to be related to survival after HR for HCC. [23][24][25][26][27][28] Several studies have compared the outcomes of LT and HR in HCC, but failed to show conclusive results 8,10,14,15,17,19 (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed, that hepatitis C virus infection is associated with increased risk of intrahepatic recurrence after HR of HCC in patients without cirrhosis. 21 However, in patients with cirrhosis, the etiology of liver disease appeared not to be related to survival after HR for HCC. [23][24][25][26][27][28] Several studies have compared the outcomes of LT and HR in HCC, but failed to show conclusive results 8,10,14,15,17,19 (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Liver Resection [7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] (Table 1) The articles reviewed for information on partial liver resection for NC-HCC include 2263 patients; the numbers of patients in these series range from 20 to 254. [7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The results of the French multicenter ...…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The results of the French multicenter study, 1 which includes the world's largest series of resections for HCC arising in normal livers (ie, nonfibrotic and noncirrhotic), are discussed separately. The larger studies come from regions with high rates of hepatitis B virus (HBV) and hepatitis C virus (HCV) infections.…”
Section: Resultsmentioning
confidence: 99%
“…GGT was utilized as a diagnostic tumor biomarker for liver disease with a high sensitivity of 83-100%, but it only has a low specificity of 32% (10). Therefore, long since GGT was not utilized as an (29,(36)(37)(38)(39)(40). The combination of GGT and other indicators, such as tumor size, tumor number, MVI, or laboratory data for AFP and DCP, should be paid more attention when deciding a treatment and predicting the curative results for patients with HCC (41).…”
Section: Ggt As a Predictive Biomarker In Clinical Investigationsmentioning
confidence: 99%